2012
DOI: 10.1590/s1415-47572012000600019
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, biogeography and divergence times in Passiflora (Passifloraceae)

Abstract: As part of a long-term investigation on the evolution of Passiflora L., we investigated the divergence ages of the genus and diversification of its subgenera, relating them with biogeographical and/or historical events, and other characteristics of this taxon. The main aim of the present work was to evaluate the biogeographic distribution of this genus to better understand its evolutionary history. This is the first time that representatives from South American and Old World Passifloraceae genera have been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 65 publications
(91 reference statements)
1
55
1
7
Order By: Relevance
“…The pattern of clustering based on the pollinic characteristics allowed to classify the species into two subgenera, Passiflora and Decaloba, congruent with the classification of Feuillet and MacDougal (2003) and supported by phylogenetic studies using molecular markers and sequencing technique (Yockteng and Nadot 2004, Hansen et al 2006, Mäder et al 2010, Porter-Utley 2014, Milwardde-Azevedo et al 2014b, Muschner et al 2012, Krosnick et al 2013, Ocampo and D'Eeckenbrugge 2017. These authors revealed that the Passiflora and Decaloba subgenera showed monophyletic clades.…”
Section: Discussionmentioning
confidence: 55%
“…The pattern of clustering based on the pollinic characteristics allowed to classify the species into two subgenera, Passiflora and Decaloba, congruent with the classification of Feuillet and MacDougal (2003) and supported by phylogenetic studies using molecular markers and sequencing technique (Yockteng and Nadot 2004, Hansen et al 2006, Mäder et al 2010, Porter-Utley 2014, Milwardde-Azevedo et al 2014b, Muschner et al 2012, Krosnick et al 2013, Ocampo and D'Eeckenbrugge 2017. These authors revealed that the Passiflora and Decaloba subgenera showed monophyletic clades.…”
Section: Discussionmentioning
confidence: 55%
“…The dendrogram favored the formation of three major groups (Figure 2 Decaloba had diversified prior to the subgenus Passiflora (Muschner et al, 2012). It explains the high molecular dissimilarity between Passiflora and Decaloba, thus accumulating molecular and morphological differences, including in modes of reproduction, flower size and number of chromosomes.…”
Section: Genetic Diversitymentioning
confidence: 89%
“…It explains the high molecular dissimilarity between Passiflora and Decaloba, thus accumulating molecular and morphological differences, including in modes of reproduction, flower size and number of chromosomes. The closeness among the species of the subgenus Passiflora is explained by its recent diversification (Muschner et al, 2012). Group II showed closeness between the two species, which indicates the potential use of interspecific crosses.…”
Section: Genetic Diversitymentioning
confidence: 92%
“…Furthermore, the contributions to molecular phylogeny may be observed in in-depth studies [16,17,18]. …”
Section: Introductionmentioning
confidence: 99%